COMPARATIVE EVALUATION OF SPECTRUM OCCUPANCY OF THE BROADCASTING BANDS IN URBAN, SUB-URBAN AND RURAL ENVIRONMENTS (Nigerian Journal of Technology, 2023)
Wireless services are at high demand all over the world, leading to increased bandwidth requirement and exhausted spectrum. In response, efforts are on-going to find ways to allow secondary access to spectrum without causing unacceptable interference issues to the Primary Users. In the fore-front of these efforts is the attempt to allow for secondary access on the TV spectrum, hence this analysis on spectrum usage measured outdoors in three locations namely Calabar in Cross River State representing an urban environment, Eket and Asong in Akwa Ibom State representing semi-urban and rural communities in Nigeria respectively. The UHF band percentage utilizations for the three locations were 98%, 76% and 33% with available cumulative bandwidths of 8MHz, 96MHz, and 264MHz respectively. Further validation of urban spectrum condition was done at Uyo in Akwa Ibom State. Findings showed that the spectrums are relatively busy in the urban and semi-urban areas whereas the economically challenging rural areas have free spectrum that can be deployed to enhance cellular broadband services at affordable rates to uplift the living standard of the dwellers.